LEGAL REGULATION OF DOUBLE TAXATION AS A HIDDEN LEGAL ELEMENT IN RUSSIA: PROBLEMATICS AND TAX CONSEQUENCES - Regina E. Witzke; Kseniya D. Grezeva; Shamil R. Zaripov (Russian Studies in Law and Politics)
The relevance of the study lies in the authors consideration of the problem of hidden double taxation in the current tax legislation of the Russian Federation. The authors have identified the problem that is observed in practice, namely its latent manifestation in various forms, leading to an increase in the tax burden on business entities and citizens. The main method of the study is an analytical review of the problem of latent double taxation within the framework of the current Tax Code of the Russian Federation. The purpose of the study is to substantiate specific examples demonstrating the presence of binary taxation, which, although not an obvious violation of the legislation, but creates significant economic costs and injustice for taxpayers, including the taxation of wages, VAT, excise duties and patent system of taxation, revealing the mechanisms through which there is a hidden double taxation of the same income. The result of the study is a proposal to solve the problem of double taxation within a comprehensive approach, including the possibility of simplifying tax rules, developing a more transparent taxation system, reducing the tax burden of taxpayers, as well as revising the structure of taxation and a clearer definition of taxation principles to prevent hidden double taxation. The key conclusion of the study is the thesis that the introduction of open and clear taxation mechanisms will improve the position of taxpayers and create a more sustainable tax environment in Russia. Further research should focus on combating double taxation, which requires careful analysis and reform of the tax system to ensure its transparency and fairness.